Atmospheres and Environments: Prolegomena to Inhabiting Sensitively - Alison, Aurosa (Aesthetica Preprint, 2020)
My attempt in this paper is to illustrate some of the major developments in current phenomenological aesthetic research in the field of Atmospheres, showing how this concept has first consolidated through phenomenological approaches and has then concretized in the context of contemporary architecture. A main issue in this regard is the theoretical-philosophical basis on which the new contexts of this project are based and are therefore marked by a sensitive and perceptive approach toward the inhabited space. Through the concepts of experience, sensitive perception, and predisposition to places I will investigate how Atmospheres today represent an aesthetic way to interpret not only the inhabited space, but also the architectural project in modern and contemporary architecture.